Pengaruh Return On Asset, Current Ratio, dan Company Size Terhadap Company Value Pada Industri Logam - Soegihartono Soegihartono; Nanang Ari Utomo (sekolah Tinggi Ilmu Ekonomi Dharmaputra Semarang, 2024)
This study aims to analyze the effect of return on asset (ROA), current ratio (CR), and company size on the value of companies in the metal and similar industrial sub-sector listed on the Indonesia Stock Exchange during the 2021-2022 period. The research was motivated by the need to understand how financial indicators and company characteristics influence the overall market value of companies in this particular industry. The hypothesis of the study was formulated based on theoretical frameworks and previous empirical research findings. To conduct this study, a purposive sampling method was employed, which involved selecting companies based on certain predetermined criteria. A total of 58 companies from the metal and related sectors were included in the sample. Data for the study was gathered from annual financial reports and analyzed using multiple linear regression techniques to test the proposed hypotheses.The results indicate that company size does not have a significant effect on the company value, suggesting that factors such as financial performance may be more crucial in determining value than the size of the company itself. However, the study found that both return on assets (ROA) and current ratio (CR) have a significant positive impact on company value. These findings emphasize the importance of efficient asset management and liquidity in increasing a company’s market value. This study contributes to a deeper understanding of the financial factors that influence the value of companies in the metal and industrial sectors and provides insights for investors and management.